New York Paper - The Coals of the Hocking Valley, Ohio - T. Sterry Hunt (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
But little was known of the coals of Southeastern Ohio until the present survey of the State under Dr. Newberry began its work. The results of the geological investigations of Prof. E. B. Andrews in this region, and of the chemical investigations of Prof. T. G. Wormley, both of which appear in the reports of the survey for 1869 and 1874, and more recent special reports by the former, together with some data for which I am indebted to the kindness of Dr. Newberry, and my own limited observations, have served me for the preparation of the following notice of the coals lying on the western border of the great Appalachian coal-basin in the region drained by the Hocking River and its tributaries, and belonging to the Lower Coal-Measures. Some uncertainty exists as to the place in the suc- ' cession of the lower coals to be assigned to the seams known and mined in the Hocking Valley. It is the opinion of Prof. Andrews that the inequalities of the original surface were such that we cannot identify in that region the lowest coals known in Northwestern Pennsylvania and the contiguous parts of Ohio, but that we must rather count from above downwards. These conclusions Dr. Newberry is not prepared to accept, and further researches will be necessary before certainty can be attained in this matter. Meanwhile it seems, from a study of its relations to the Pomeroy or Pittsburgh seam, that what is known as the great vein of the Hocking Valley, occupies the horizon of the Upper Freeport coal, E of the Pennsylvania survey, or No. 6 in Dr. Newberry's enumeration, counting from the base. This seam, in the region in question. assumes certain characteristics which, taken in connection with its geographical position, give it a great importance among the coals of the State. The area to be noticed includes the whole or parts of several townships in Perry, Hocking, Vinton, and Athens Counties, lying near the margin of the basin over which the vein in question assumes the character of a dry-burning or splint coal, and has a thickness varying from six to ten and even twelve feet. Its precise limit southward cannot at present be clearly defined, but it has been found as far south as the line of the Marietta and Cincinnati Railroad, with a thickness of six feet, and is mined at various points along the valley of the Hocking River, near Nelsonville, where it attains six or seven feet. To the northward, along the tributaries of this river, Sunday and Monday